BIOECOLOGY OF RHINOCORIS FUSCIPES FABR. (REDUVIIDAE) A POTENTIAL PREDATOR ON INSECT PESTS - AMBROSE, DUNSTON P.; LIVINGSTONE, DAVID (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
Rhinocoris fuscipes Fabr, starts laying maroon coloured elongate eggs in batches at the age of 28-3 days. Eggs are glued to each other and to the substratum with cementing material. Eggs hatch in eight days, Nymphs are orange red with yellowish green legs bearing brown spots which simulate panther's skin. Stadial period from first instar to adult ranges from 38-50 days. Adult females live longer than the males. Out of two generations raised in the laboratory males and females emerge in the sex ratio 1 : 2. R. fuscipes is found to be predating on pests of cotton and maize both in the field and laboratory conditions.